Precision agriculture in avocado production: Mapping the landscape of scientific and technological developments - Taramuel-Taramuel, Juan P.; Jiménez-Hernández, Claudia Nelcy; Barrios, Dursun (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2024)
The integration of cutting-edge precision agriculture technologies into avocado production is a promising strategy to boost productivity and profitability in this thriving industry. While previous reviews have explored the application of emerging technologies in avocado cultivation, there is a gap in the analysis of patent production. This research aims to bridge that gap by identifying trends in both scientific and technological innovations related to precision agriculture in avocado. Through a bibliometric analysis using data from Scopus and Lens.org, this study reveals that scientific production is primarily concentrated in industrialized countries, with limited research output from major avocado-producing nations. The focus of research has been on remote sensing and image processing techniques. In terms of technological development, innovations in agricultural data capture, collection, and processing, as well as components for agricultural machinery, have been the most prevalent. Market-available technologies are designed to predict crop yields and assess the impact of abiotic factors such as temperature, humidity, and precipitation. By adopting these precision agriculture tools, avocado farmers can make data-driven decisions to optimize resource use, improve crop health, and ultimately enhance overall farm performance.